Deep learning based automated diagnosis of Ocular Toxoplasmosis in fundus images using convolutional neural network - Choudhury, Prionto Kumar; Anika, Asma Akter; Ramisa, Sumaiya Rahman; Zaman, Arsi; Chowdhury, Rizvee Rifat (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2024.